THE RELATIONSHIP BETWEEN KNOWLEDGE AND USE OF COMPLEMENTARY THERAPIES AND BLOOD PRESSURE MEASUREMENTS IN HYPERTENSIVE PATIENTS - Fradana Ade Saputra; Dwi Sri Handayani; Sriyati (Keperawatan Anestesiologi Program Sarjana Terapan, 2024)
ABSTRACT Background: Prolonged high blood pressure can damage blood vessels in vital organs such as the heart, kidneys, brain, and eyes. Therefore, patient knowledge of complementary therapies is essential as it can guide them in selecting effective treatment methods, such as complementary therapies that help lower blood pressure. This underscores the need for further research among hypertensive patients. Methods: This study used an analytical correlational research design with a cross-sectional approach and employed total sampling of 79 participants. Data were collected using a questionnaire on knowledge of complementary therapies for hypertension and an interview sheet on the use of complementary therapies. Statistical analysis was performed using Kendall's Tau. Results: The majority of respondents had good knowledge of complementary therapies (62 or 78.3%), used the therapy effectively (75 or 94.9%), and 60 (75.9%) had stage 1 hypertension. The hypothesis test results between knowledge of complementary therapies and blood pressure showed a p-value of 0.084. However, the hypothesis test between the use of complementary therapies and blood pressure revealed a p-value of 0.001, and the test between knowledge and use of complementary therapies yielded a p-value of 0.002. Conclusion: There was no significant relationship between knowledge of complementary therapies and blood pressure measurements. However, a significant relationship was found between the use of complementary therapies and blood pressure, as well as between knowledge and the use of complementary therapies. Further research and educational initiatives are recommended to improve patient adherence to complementary therapy practices.